2020
DOI: 10.1101/2020.11.02.359992
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Control of neurogenic competence in mammalian hypothalamic tanycytes

Abstract: Hypothalamic tanycytes, radial glial cells that share many features with neuronal progenitors, can generate small numbers of neurons in the postnatal hypothalamus, but the identity of these neurons and the molecular mechanisms that control tanycyte-derived neurogenesis are unknown. We report that tanycyte-specific disruption of the NFI family of transcription factors (Nfia/b/x) stimulates proliferation and tanycyte-derived neurogenesis. Single-cell RNA- and ATAC-Seq analysis reveals that NFI factors repress … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 94 publications
1
6
0
Order By: Relevance
“…Rax- negative frizzy cells expressing tdTomato were more broadly distributed, suggesting that frizzy cells move over long distances and downregulate Rax while migrating. Frizzy cells were also observed by other studies, such as by Yoo and colleagues [ 16 ] who used the same Rax-CreERT2 /+ line, and showed a reporter-positive cell with glial cell-like morphology that is identical to a frizzy cell. Another tanycyte lineage-tracing study using Fgf10-CreERT2 /+ mice described reporter-positive glial-like cells [ 40 ] that are morphologically identical to frizzy cells.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Rax- negative frizzy cells expressing tdTomato were more broadly distributed, suggesting that frizzy cells move over long distances and downregulate Rax while migrating. Frizzy cells were also observed by other studies, such as by Yoo and colleagues [ 16 ] who used the same Rax-CreERT2 /+ line, and showed a reporter-positive cell with glial cell-like morphology that is identical to a frizzy cell. Another tanycyte lineage-tracing study using Fgf10-CreERT2 /+ mice described reporter-positive glial-like cells [ 40 ] that are morphologically identical to frizzy cells.…”
Section: Discussionsupporting
confidence: 76%
“…However, frizzy cells may represent a subtype of protoplasmic astrocytes with low GFAP expression/immunoreactivity [ 30 , 41 ], and potentially with neural progenitor characteristics akin to a subtype of hippocampal astrocytes [ 42 ]. In a recent RNA-Seq study that categorized cells of the Rax lineage, frizzy cells were probably classified as astrocytes and/or oligodendrocyte precursor cells, and it was noted that astrocytes appear to arise directly from α1 and α2 tanycytes [ 16 ]. Interestingly, we observed that dorsal α1 tanycytes translocated into the parenchyma with nearby RAX + frizzy cells ( Figure 2B2 inset), which may offer a snapshot into the process of tanycytes entering the parenchyma and differentiating into frizzy cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Congenital metabolic disorders and obesity can result from Mendelian mutations in transcription factors that control hypothalamic patterning (Blanchet et al, 2017;Holder et al, 2000), and mutations in genes identified as important for controlling hypothalamic and neurogenesis in this study may contribute to multigenic disorders that may have a hypothalamic origin, such as Type 2 diabetes, sleep disorders, and depression (Bao et al, 2008;Biran et al, 2015;Dearden and Ozanne, 2015). Understanding the molecular mechanisms controlling early hypothalamic development is also critical to efforts towards induced differentiation of specific hypothalamic neuronal subtypes from embryonic stem (ES) or induced pluripotent stem (iPS) cells (Merkle et al, 2015;Nagasaki et al, 2015;Seifinejad et al, 2019;Wang et al, 2016), as well as for directed reprogramming of hypothalamic glial cells (Kano et al, 2019;Yoo et al, 2021). Cell-based approaches such as these may ultimately hold the potential for the directed rewiring of core hypothalamic regulatory circuitry for treating a broad range of homeostatic disorders.…”
Section: Discussionmentioning
confidence: 91%